MedBulletin - Yu, James; Chen, Kevin (The Meducator, 2018)
This issue’s MedBulletin includes Oubain: From Poison to Contraceptive, A New Promise in Cancer Immunotherapy, Unearthing New Antibiotics, and Diabetes - Blood, Sweat, and Tears.